(untitled) (Environment & Health, 2025)
The aim of the article is to identify heavy metals that can be potential soil pollutants as a result of shelling, rockets, and other weapons, as well as ways to monitor heavy metals. Materials and methods: an analytical review of scientific information resources, the topics of which correspond to the purpose of this article, was carried out. Scientific publications of domestic and foreign scientists were searched using the PubMed and Google Scholar databases for 1997-2014 under determination by the keywords «war», «armed conflict», «soil pollution», «chemical pollution», «metals», «semi-metals», «environment», «health», «ecocide», «monitoring». Results and discussion. There are various sources of metals in firearms residues, including shell casings (Pb, Sb, Ba), metal jacketed bullets (Cu, Zn) and barrels (Fe). Explosives also play a significant role in the release of metals into the environment, as the particles ejected from artillery strikes contain high levels of Pb and Cu. Explosive grenades are also considered a significant source of high Pb concentrations. Military activities, especially in conditions of armed conflicts, lead to soil contamination with Pb and Cu, as well as other metals including Cd, Sb, Cr, Ni, Zn, with subsequent movement of metals into water, thus increasing the risk of human exposure. In various countries, biomonitoring studies of territories where military operations took place showed increased accumulation of metals in plants, invertebrates, and some species of vertebrates (fish, birds, mammals). The degree of soil contamination with metals can be monitored with the help of plants, which are good indicators of the soil conditions in which they grow. Plant tops are collectors of air pollutants, and their chemical composition can be a good indicator for polluted areas when compared with background values obtained for unpolluted vegetation. Aquatic and terrestrial plants are known to bioaccumulate heavy metals and are therefore a potential source of these pollutants for the human food chain. Conclusions. Establishing the ways of including heavy metals in food chains and, accordingly, analyzing their amount in soil layers and plants, can help to develop monitoring methods for war-damaged territories of Ukraine aimed at preventing the further impact of soil pollutants on humans and the environment. In turn, mechanisms for more effective environmental restoration can be developed.